Anti-Mutant Efficacy of Combination Therapy with Doripenem and Levofloxacin: In Vitro Model Studies with Pseudomonas Aeruginosa - M. V. Golikova; E. N. Strukova; K. N. Alieva; A. V. Filimonova; Yu. A. Portnoy; A. A. Firsov (Антибиотики и Химиотерапия)
Relevance. The tendency to a decrease in sensitivity of bacterial agents to old antibiotics, as well as the slowdown in creation of new medications, dictate the need to develop effective approaches to combat bacterial resistance.Aim. Evaluation of the applicability of a pharmacokinetically-based approach to predicting anti-mutant effectiveness of combined therapy with doripenem and levofloxacin against gram-negative bacteria Pseudomonas aeruginosa.Material and methods. A collection strain of Pseudomonas aeruginosa was used in the study. The values of MPC (mutant prevention concentration) of the combination of doripenem and levofloxacin were evaluated at a ratio of their concentrations equal to therapeutic ratios of the area under the pharmacokinetic curve in the in vitro dynamic model. 5-day treatments with clinical doses of doripenem and levofloxacin individually and in combination were simulated. Bacteria-containing medium was sampled during the experiments and plated on agar media containing 2MIC of each antibiotic.Results. The MPCs of doripenem and levofloxacin decreased 4 times when used in combination compared to MPC values when used separately. P.aeruginosa population was enriched with resistant mutants during monotherapy with each medication; the number of the bacteria did not decrease or even increased by the end of observation period. The use of doripenem/levofloxacin combination completely prevented development of resistance to both drugs in P.aeruginosa. The observed anti-mutant effect of antibiotic combination was consistent with higher (compared to monotherapy) values of the time during which the concentration of the antibiotic exceeded MPC (T>MPC).Conclusion. The anti-mutant effectiveness of combined therapy with doripenem and levofloxacin increased with the decrease in the values of MPC of antibiotics when used simultaneously, which consequently led to the increase in the values of T>MPC. Obtained results confirm the applicability of a pharmacokinetically-based approach to the estimation of MPC of combined antibiotics for predicting anti-mutant effectiveness of combination therapy in the treatment of infections caused by gram-negative bacteria.